Hybrid particles derived from alendronate and bioactive glass for treatment of osteoporotic bone defects - Diba, Mani; Camargo, Winston A.; Zinkevich, Tatiana; Grünewald, Alina; Detsch, Rainer; Kabiri, Yoones; Kentgens, Arno P. M.; Boccaccini, Aldo R.; Van Den Beucken, Jeroen J. J. P.; Leeuwenburgh, Sander C. G. (Journal of Materials Chemistry B, 2019)
Osteoporosis is the most widespread metabolic bone disease which represents a major public health burden. Consequently, novel biomaterials with a strong capacity to regenerate osteoporotic bone defects are urgently required. In view of the anti-osteoporotic and osteopromotive efficacy of alendronate and 45S5 bioactive glass, respectively, we investigated the feasibility to synthesize novel hybrid particles by exploiting the strong interactions between these two compounds. Herein, we demonstrate the facile preparation of a novel class of hybrid particles of tunable morphology, chemical composition and structure. These hybrid particles (i) release alendronate and various inorganic elements (Ca, Na, Si, and P) in a controlled manner, (ii) exhibit a strong anti-osteoclastic effect in vitro, and (iii) stimulate regeneration of osteoporotic bone in vivo. Consequently, this novel class of hybrid biomaterials opens up new avenues of research on the design of bone substitutes with specific activity to facilitate regeneration of bone defects in osteoporotic patients.
CRIS-Team Scopus Importer:2019-07-19